1983
DOI: 10.1017/s0003356100010527
|View full text |Cite
|
Sign up to set email alerts
|

Food intake, growth and mature size in Australian Merino and Dorset horn sheep

Abstract: The pattern of food intake as a function of age, and live weight as a function of food consumed was examined from soon after weaning to maturity in groups of fine and strong wool Merino rams and Dorset Horn rams and wethers. Each group, which initially comprised 20 sheep and from which individuals were removed for slaughter at approximately 6-kg increments in live weight, was fed a pelleted ration ad libitum for 98 and 77 weeks for the Merino and Dorset Horn groups respectively.The pattern of food intake was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
2
2
0
1
Order By: Relevance
“…The effect of food on efficiency was expected from the food compositions (Table 1) and reflected both slower growth and higher food intake on L compared with H. Food efficiency was independent of sex in this trial in agreement with other studies (McClelland et al, 1973;Thonney et al, 1987a). The same authors and Thompson and Parks (1983) also found no overall breed effects on efficiency. There was evidence that the breeds used here differed in their response to the different foods: efficiency was reduced in all breeds on L compared with H but to a greater extent in the Suffolk (ratio L : H~0-463) than the Scottish Blackface (0·606).…”
Section: Lite Performancesupporting
confidence: 91%
“…The effect of food on efficiency was expected from the food compositions (Table 1) and reflected both slower growth and higher food intake on L compared with H. Food efficiency was independent of sex in this trial in agreement with other studies (McClelland et al, 1973;Thonney et al, 1987a). The same authors and Thompson and Parks (1983) also found no overall breed effects on efficiency. There was evidence that the breeds used here differed in their response to the different foods: efficiency was reduced in all breeds on L compared with H but to a greater extent in the Suffolk (ratio L : H~0-463) than the Scottish Blackface (0·606).…”
Section: Lite Performancesupporting
confidence: 91%
“…Despite breed and sex having large effects on absolute, and scaled, gains and intakes, there were no breed or sex effects on food efficiency. 'This is in agreement with results of previous studies (McClelland et al, 1973;Butterfield et al, 1983;Thompson and Parks, 1983;Thonney et al, 1987;Lewis et al, 2004b).…”
Section: Live Performancesupporting
confidence: 94%
“…However, ADG was similar in all groups showing that lthose weaned with less weight did not have a catching up growth. As post-weaning growth of lambs depends on solid food intake as well as on their genetically potential for growth (NAGPAL et al, 1994), weaning weight is an important factor for later growing because the increase of live weight is reduced in relation to food intake when animals approach to maturity (THOMPSON & PARKS, 1983).…”
Section: Ciência Rural V38 N3 Mai-jun 2008mentioning
confidence: 99%